Cohesion, adaptability and family composition in adolescents of Callao, Peru - Villarreal-Zegarra, David (2017)
The objective of the study was to analyze if there are significant differences between family cohesion and adaptability according to the type of family composition (nuclear, extensive, single parent and anuclear). This is an experimental, non-experimental, empirical research in which a non-probabilistic and cross-sectional selective associative strategy was employed; 428 male and female teenagers, aged 14 to 18, were evaluated at a national school in Callao. The scale of evaluation of cohesion and family adaptability of D. Olson (FACES III) and an ad hoc questionnaire to evaluate family composition were used. The results show significant differences between adolescents belonging to nuclear and anuclear families. Theoretical and practical implications are discussed.